Gallic acid alleviates lipopolysaccharide-induced renal injury in rats by inhibiting cell pro-death and inflammatory response and its mechanism: Gallic acid mitigates LPS-induced renal injury in rats - Luan, Xin; Ou, Wen; Hu, Jing; Lu, Jianrao (Cellular and Molecular Biology, 2023)
The mechanism of gallic acid in improving lipopolysaccharide-induced renal injury in rats was investigated by studying the pro-death and inflammatory response of cells. SPF rats were randomly divided into 4 groups with n=10 in each group. Blank control group: normal saline injection; The model group was injected with LPS induced model (LPS group); Low dose gallic acid group (LPS+L-GA group); Middle dose gallic acid group (LPS+M-GA group). The expression of serum inflammatory factors IL-1, IL-1β, IL-18, and MCP-1 were detected by Elisa. Western blot assay was used to detect the expression of inflammation-related proteins. The contents of BUN, Scr, SUA, Serum cystatinALB, and ACR were determined by the biochemical analyzer. The pathological tissue sections were used to observe the kidney injury in each group. The renal expressions of NLRP3, Caspase-1, GSDMD, and IL-1β were detected by immunohistochemistry. The activation of the AMPK/SIRT1 signaling pathway was detected by Western blot assay. The LPS-induced mouse kidney injury model was established successfully. Compared with the model group, different doses of gallic acid can improve the expression of renal biochemical indexes (P<0.05); At the same time, gallic acid can activate AMPK/SIRT1 and reduce kidney injury in mice (P<0.05); Compared with the model group, the expression of pyroptosis gene, the expression of genes related to inflammatory factors and the expression of inflammatory factors were decreased in the gallic acid injection group (P<0.05). By activating the AMPK/SIRT1 signaling pathway, gallic acid can inhibit the scorch death and validation effect in mice, thereby protecting the kidneys of mice.